Catheter insertion depths in less-invasive surfactant administration. Issue 2 (3rd June 2021) - Maiwald, Christian Achim; Neuberger, Patrick; Franz, Axel R; Engel, Corinna; Michel, Jörg; Esser, Michael; Poets, Christian F
Abstract : Introduction: Less-invasive surfactant administration (LISA) under continuous positive airway pressure is increasingly used for the treatment of neonatal respiratory distress. Different procedures are described, but data on the optimal catheter insertion depth are sparse. Objective: To generate data for recommending an optimal catheter insertion depth in LISA. Methods: We examined 112 anterior–posterior chest X-rays from intubated infants and determined the carina's vertebral projection, whenever possible. After that, distances between the middle of cervical vertebra 4 (C4) and thoracic vertebra 2 and the middle of C4 to thoracic vertebra 3, respectively, were measured. Results were plotted against infant's weight. Results: A weight-based chart and recommendations for the optimal intratracheal catheter position in infants with a body weight between 350 and 4000 g were created. Conclusions: Generated data offer standardisation and may thus help to find a balance between risk of surfactant reflux and unilateral surfactant administration.